SGK1 mutation status can further stratify patients with germinal center B‐cell‐like diffuse large B‐cell lymphoma into different prognostic subgroups. (1st February 2022) - Guo, Baoping; Huang, Yujie; Duan, Ying; Liao, Chengcheng; Cen, Hong
Abstract: There are over a 100 driver gene mutations in patients with diffuse large B‐cell lymphoma (DLBCL), but their clinical significance remains unclear. Here, we first analyzed the DLBCL dataset from the UK‐based Haematological Malignancy Research Network. Patients were divided into high‐ and low‐risk groups based on whether lymphoma progressed within 24 months. Genes showing significantly different frequencies between groups were selected. Survival data for patients with the selected mutant genes were analyzed. The results were validated using two other large databases to evaluate the relationship between the selected mutant genes and prognosis. The mutation frequencies of 11 genes ( MYD88 [L265P], SGK1, MPEG1, TP53, SPEN, NOTCH1, ETV6, TNFRSF14, MGA, CIITA, and PIM1 ) significantly differed between the high‐ and low‐risk groups. The relationships between these mutant genes and patient survival were analyzed. Patients who harbored SGK1 (serum and glucocorticoid‐inducible kinase 1) mutations exhibited the best prognosis. Most patients with SGK1 mutation are germinal center B‐cell (GCB) subtype. Among patients with GCB DLBCL, those harboring SGK1 mutations exhibited better prognosis than those without SGK1 mutations. Most SGK1 mutations were single‐base substitutions, primarily scattered throughout the catalytic domain‐encoding region. Multiple SGK1 mutations were identified in a single patient. Thus, SGK1 mutations are a marker of good prognosis for DLBCL and occur predominantly in the GCB subtype of DLBCL. SGK1 mutation status can further stratify patients with GCB DLBCL into different prognostic subgroups. Abstract : We believe that our study makes a significant contribution to the literature and will be of interest to the readership of your journal, because it provides strong evidence that mutations in serum and glucocorticoid‐inducible kinase 1 (SGK1) are associated with better prognosis in patients with diffuse large B‐cell lymphoma and, thus, that targeting SGK1 may improve patient prognosis.